Numerical distribution functions of fractional unit root and cointegration tests - James G. MacKinnon; Morten Ørregaard Nielsen (Queen's University, Department of Economics, 2010)
We calculate numerically the asymptotic distribution functions of likelihood ratio tests for fractional unit roots and cointegration rank. Because these distributions depend on a real-valued parameter, b, which must be estimated, simple tabulation is not feasible. Partly due to the presence of this parameter, the choice of model specification for the response surface regressions used to obtain the numerical distribution functions is more involved than is usually the case. We deal with model uncertainty by model averaging rather than by model selection. We make available a computer program which, given the dimension of the problem, q, and a value of b, provides either a set of critical values or the asymptotic P value for any value of the likelihood ratio statistic. The use of this program is illustrated by means of an empirical example involving opinion poll data.
Keywords: C12; C16; C22; C32; 330; cofractional process; fractional unit root; fractional cointegration; response surface regression; cointegration rank; numerical distribution function; model averaging; Unit Root Test